KEBIASAAN DAN KECANDUAN MAKAN PINANG MASYARAKAT DUA KOTO KABUPATEN PASAMAN SEBAGAI OBAT PENGHILANG BAU MULUT - Wilda Hayati (SEMESTA: Journal of Science Education and Teaching, 2022)
Arecanut is a crop with many benefit, but has not yet been considered a special commodity. Betelnut production can reach 50-100/ spadix and 150-250 / spadix for the size of smaller fruit. In 2003 areca exporting volume reached to 77 126 347/kg with value of US$ 22 960 446. The tanin and alkaloid content are two dominant compound at areca seed. Tanin content about 15%, as a compound of polifenol which can in dissolve alcohol and gliserol, while alkaloid 0,3-0,6%. Using of betelnut as messed together with ingredient piper betel have come to habit hereditaryly at some certain area in Indonesia, but its limited consumer. Empirically, areca seed can overcome various disease type. Various benefit able to be obtained from using of seed propose to shall be as follows 1) as requirement of fundamental, source of energy and for the ceremony, 2) in the place of cigarette, arranging digestion and prevent sleepily, 3) cosmetic and slender 4) raw material of drug, and 5) as antidepresi.